All that glisters is not gold - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The flow of remittances from migrant communities into ACP countries was once seen as a key to the balance of payments. But how much do they, could they, mean to agriculture? Posters and billboards advertising money transfers are now part of most...